2020
DOI: 10.1177/1079063220981906
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Focused Conceptualization of Collateral Consequences Among Individuals Who Sexually Offend: A Systematic Review

Abstract: Despite speculation regarding the role of collateral consequences of sexual offender policies in psychosocial and criminogenic outcomes, there has been no empirical analysis in the extant literature examining these links. Lack of conceptual underpinnings and no psychometrically valid measure of collateral consequences has limited study in this area. A systematic literature review was conducted to assess the state of measurement in terms of conceptual and operational definitions, populations sampled, domains as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 44 publications
(125 reference statements)
0
11
0
4
Order By: Relevance
“…Few studies assessing collateral consequences report scale reliabilities (e.g., Call, 2017, 2018; Harris et al, 2015), whereas no studies referenced indicators of validity or how validity may have been assessed in the process of scale development. Similar limitations noted in the current state of collateral consequences measurement included broad/limited response scales (sacrificing nuance), limited information regarding item development, and little discussion regarding definitional or conceptual underpinnings of collateral consequences (Hamilton, 2020). Results from the systematic review of collateral consequences measures highlighted the need not only for psychometrically valid measurement but for a unified conceptualization of collateral consequences with which to guide instrument development.…”
Section: Measurement Considerationsmentioning
confidence: 99%
See 4 more Smart Citations
“…Few studies assessing collateral consequences report scale reliabilities (e.g., Call, 2017, 2018; Harris et al, 2015), whereas no studies referenced indicators of validity or how validity may have been assessed in the process of scale development. Similar limitations noted in the current state of collateral consequences measurement included broad/limited response scales (sacrificing nuance), limited information regarding item development, and little discussion regarding definitional or conceptual underpinnings of collateral consequences (Hamilton, 2020). Results from the systematic review of collateral consequences measures highlighted the need not only for psychometrically valid measurement but for a unified conceptualization of collateral consequences with which to guide instrument development.…”
Section: Measurement Considerationsmentioning
confidence: 99%
“…A systematic review of the collateral consequences measurement literature, recently conducted by Hamilton (2020), found that studies have primarily reported descriptive data intending to demonstrate the impact of collateral consequences by using sheer numbers (Hamilton, 2020). That is, items tend to broadly target housing restrictions (e.g., “I had to move out of a home I owned”; Levenson, 2008), employment difficulties (e.g., “I lost a job because my boss or coworkers found out I am a sex offender”; Levenson & Cotter, 2005a), interpersonal problems (e.g., “I feel that my close relationships [friendships, family ties] have suffered because I am listed on the sex offender registry”; Klein & Bailey, 2016), and psychological consequences (e.g., “I feel alone and isolated because of Megan’s Law; Levenson & Cotter, 2005a).…”
Section: Measurement Considerationsmentioning
confidence: 99%
See 3 more Smart Citations